2007
DOI: 10.1590/s0103-84782007000600053
|View full text |Cite
|
Sign up to set email alerts
|

Composição corporal e crescimento de juvenis de piava alimentados com dietas contendo farinhas de trigo e milho submetidas ao cozimento

Abstract: RESUMO Neste trabalho, foi avaliado o efeito do cozimento das farinhas de milho e trigo na composição corporal ABSTRACT This study was aimed at evaluating the cooking effect in corn and wheat flours in the body composition and growth of piava. They were used 300 juveniles (Initial weight=8.03 ± 0.02g), fed for 60 days, once a day (3%BW). The basal diet was constituted by only matrix, being the treatments designated: diet B (without cooking), M (cooked corn flour), T (cooked wheat flour) and diet MT (both cooke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…When several specimens of Leporinus obtusidens were subjected to dietary feeding with and without cooking, the results referring to protein are similar and lower for the percentage of ashes. Considering that the fish feed of the present study was different from the one used by the mentioned author, the evaluated parameters show a quite similar behavior (Lazzari et al 2007). Although the ash values of Warakú verdadero and Warakú pinima resemble different species, they are superior to the values found for fillets of Pacú (Piaractus mesopotamicus) (~1.20%) (Pavón et al 2018) Although no statistically significant differences were found in the present study (p > 0.05) related to the hydrobiological cycle in the different capture sites, it should be considered that the factors that affect the chemical/nutritional composition of the fish are numerous, being either an intrinsic nature bearing upon genetics, morphology, physiology or environmental factors, relating to the living conditions and food (Jacquot 1961;Borgstrom 2012).…”
Section: Leporinus Fasciatusmentioning
confidence: 77%
“…When several specimens of Leporinus obtusidens were subjected to dietary feeding with and without cooking, the results referring to protein are similar and lower for the percentage of ashes. Considering that the fish feed of the present study was different from the one used by the mentioned author, the evaluated parameters show a quite similar behavior (Lazzari et al 2007). Although the ash values of Warakú verdadero and Warakú pinima resemble different species, they are superior to the values found for fillets of Pacú (Piaractus mesopotamicus) (~1.20%) (Pavón et al 2018) Although no statistically significant differences were found in the present study (p > 0.05) related to the hydrobiological cycle in the different capture sites, it should be considered that the factors that affect the chemical/nutritional composition of the fish are numerous, being either an intrinsic nature bearing upon genetics, morphology, physiology or environmental factors, relating to the living conditions and food (Jacquot 1961;Borgstrom 2012).…”
Section: Leporinus Fasciatusmentioning
confidence: 77%